Hybrid Electronic Watt-Hour Meter. (1980) - Trontelj, J.; Trontelj, L.; Jan, F.; Hrovat, M.
Abstract : An electronic watt–hour meter in hybrid thick and thin film technology is described. Benefits of combined hybrid technologies are evaluated. Methods for offset voltage and multiplier modulation frequency are given. The hybrid circuit with the 10 −5 linearity for a 0.1 class electricity meter is shown.